2012
DOI: 10.5935/0101-2800.20120027
|View full text |Cite
|
Sign up to set email alerts
|

RIFLE Classification: prospective analysis of the association with mortality in critical ill patiants

Abstract: The severity of AKI according to RIFLE criteria was a risk marker for mortality in this population. The LRA group class Injury + Failure was associated with increased mortality when compared to the subgroup Without AKI + AKI that remained in Risk class even after adjustments for multiple variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The SOFA score was reported in 21 and 10 studies from developed and developing countries, respectively. The distribution of the SOFA score was similar between groups, ranging from 3 [25] to 13.4 [26] in studies from developed countries and from 3 [27] to 9.8 [28] in developing country studies. In studies where this information was available, a SOFA score over 5 was reported by 71% (15/21) of studies from developed countries and 80% (8/10) of studies in developing countries (Tables 6 and 7).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…The SOFA score was reported in 21 and 10 studies from developed and developing countries, respectively. The distribution of the SOFA score was similar between groups, ranging from 3 [25] to 13.4 [26] in studies from developed countries and from 3 [27] to 9.8 [28] in developing country studies. In studies where this information was available, a SOFA score over 5 was reported by 71% (15/21) of studies from developed countries and 80% (8/10) of studies in developing countries (Tables 6 and 7).…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…Two studies found incidences of 25.5% ( Ponce et al., 2011 ) and 39.3% ( Nisula et al., 2013 ) using AKIN classification. Other authors reported an incidence range of 35.7–47.0% by using the Risk/Injury/Failure/Loss/End-stage (RIFLE) system ( Bagshaw et al., 2008 ; Wahrhaftig, Correia & De Souza, 2012 ; Mohamed et al., 2013 ). In a prospective study including 29,269 patients hospitalized at 54 ICUs from 23 countries, Uchino et al.…”
Section: Discussionmentioning
confidence: 99%
“…Bivariate analysis highlighted the relevant risk factors for AKI that have been investigated individually or in combination by other observational studies ( Mataloun et al., 2006 ; Prakash et al., 2006 ; Taber & Mueller, 2006 ; Bagshaw et al., 2008 ; Perazella, 2012 ; Wahrhaftig, Correia & De Souza, 2012 ; Wang et al., 2012 ; Herrera-Gutiérrez et al., 2013 ; Mohamed et al., 2013 ). We found that typical risk factors were associated with AKI in the studied patients, including advanced age, higher APACHE II score at admission to ICU, sedation, mechanical ventilation, and infection.…”
Section: Discussionmentioning
confidence: 99%
“…GFR-and serum creatinine measurements and definition of acute kidney injury GFR (MDRD (modification of diet in renal disease) formula) and serum creatinine were measured in all patients before TAVI (b2 days) and after TAVI at the day of the procedure and then continuously until discharge (mean hospital stay was 16.8 ± 12.2 days). The occurrence of AKI during hospitalization was defined according to the Rifle classification [16]. In this classification, AKI is defined as a decrease of GFR by more than 50% or a 2 fold increase in serum-creatinine.…”
Section: Patientsmentioning
confidence: 99%